Green preparation of porous hierarchical TiO2(B)/anatase phase junction for effective photocatalytic degradation of antibiotics. Issue 96 (22nd November 2021) - Wang, Qian; Fang, Xinxin; Hao, Pin; Chi, Wenwen; Huang, Fang; Shi, Xifeng; Cui, Guanwei; Liu, Yuan; Tang, Bo
Abstract : Novel porous hierarchical TiO2 (B)/anatase phase junction was controllably prepared by a green "designer" DES, and it could efficiently remove multiple kinds of resistant organic pollutants. Abstract : In this study, porous hierarchical bronze/anatase phase junction TiO2 assembled by ultrathin two-dimensional nanosheets was prepared by a novel, green and simple deep eutectic solvent-regulated strategy. Due to its structural features, the TiO2 sample exhibited enhanced photocatalytic activities for multiple kinds of antibiotics, including ofloxacin, ciprofloxacin and chloramphenicol.